O incidente de desconsideração da personalidade jurídica na execução fiscal - Giannico Neto, Francisco Ettore (2019)
The object of the present study consists in the legislative, doctrinal and jurisprudential analysis of the application of the incident of disregard of legal entity in the context of tax execution procedure. We intend to analyze the theory of the disregard of the legal entity, demonstrating that its institute differs from the passive tax subjection (either from taxpayers, from the responsible) and from the direct responsibility of the partner for the irregular dissolution of a society. The disregard of the legal entity is an exceptional measure in Private Law, derives from the principle of the separation of assets conferred to legal entities and the principle of patrimonial liability. It is a reasonable instrument in the fiscal execution, within specific hypotheses, to achieve the equity of the managing partner of the taxpayer. In order to preserve the constitutional guarantees of due process, the contradictory and the full defense, we intend to demonstrate that third party liability not included in the executive title of the tax execution must be preceded by the proper procedural incident for its recognition, recently established by the Code of Civil Procedure